Anlotinib for previously treated advanced or metastatic esophageal squamous cell carcinoma: A double‐blind randomized phase 2 trial - Huang, Jing (Cancer Med, 2021)
BACKGROUND: Currently, there are no randomized trials on the effect of antiangiogenic therapy in patients with esophageal squamous cell carcinoma (ESCC). The following study investigated the efficacy and safety of anlotinib in patients with advanced ESCC who were previously treated with chemotherapy. METHODS: This randomized, placebo‐controlled, double‐blind phase 2 trial (NCT02649361) was conducted in 13 Chinese hospitals. Eligible patients were adults with histologically confirmed recurrent or metastatic ESCC who were previously treated with chemotherapy, and were randomly assigned (2:1) to receive oral anlotinib 12 mg or placebo on days 1–14 (repeated every 21 days). The primary endpoint was progression‐free survival (PFS). RESULTS: One hundred and sixty‐five patients were randomly assigned to the anlotinib (n = 110) or the placebo (n = 55) arm. Median PFS was 3.02 months (95% CI 2.63–3.65) in the anlotinib group and 1.41 months (95% CI 1.38–1.41) in the placebo group (hazard ratio 0.46 [95% CI 0.32–0.66]; p < 0.001). The most common treatment‐related adverse events of grade 3 or 4 were hypertension (17 [16%] patients), decreased appetite (6 [6%] patients), and hyponatremia (4 [4%] patients) in the anlotinib group and decreased appetite (2 [4%] patients) in the placebo group. Three (3%) deaths in the anlotinib group were considered as drug related, while there were no treatment‐related deaths in the placebo group. CONCLUSIONS: The use of anlotinib in previously treated, recurrent, or metastatic ESCC patients significantly improved PFS compared with placebo. Our findings suggest that antiangiogenesis might be an important therapeutic target in advanced ESCC. CLINICAL TRIALS REGISTRATION: Study of Anlotinib in Patients With Esophageal Squamous Cell Carcinoma (ALTER1102), NCT02649361.